MUNASABAH SURAT AL-FIL DAN QURAISH PERSPEKTIF FAKHR AL-DIN AL-RAZI: REFLEKSI ATAS KEAMANAN DAN TANGGUNG JAWAB SOSIAL: THE MUNĀSABAH OF SŪRAT AL-FĪL AND SŪRAT QURAYSH IN THE PERSPECTIVE OF FAKHR AL-DĪN AL-RĀZĪ: A REFLECTION ON SECURITY AND SOCIAL RESPONSIBILITY - Jaka Ghianovan; Agusman Armansyah; Hilman Rosidi; M. Abdul Ghafur (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The study of Munāsabah in the Qur'an not only aims to uncover the structural coherence between verses and suras, but also serves as a means to explore the social and ethical messages embedded in the text. This article examines the munāsabah between Surah al-Fil and Surah Quraysh from the perspective of Fakhr al- Din al-Razi as presented in his commentary Mafatih al-Ghayb. This research uses qualitative methods with a library-based approach, utilizing primary and secondary sources. The findings indicate that al-Razi considered the two suras to be closely related, both as a unified thematic entity and as two distinct suras that remain conceptually interconnected. The narrative of the destruction of the elephant army in Surah al- Fil is interpreted as a manifestation of divine protection over Mecca, which is then followed by the affirmation of the Quraysh as a community blessed with security, economic stability, and social prestige. This Munāsabah underscores that this privilege is not absolute, but is accompanied by ethical demands in the form of social responsibility and devotion to God. Therefore, this study shows that munāsabah in al- Razi's interpretation goes beyond textual coherence to reflect the values of security and social responsibility in collective life.